2022
DOI: 10.3390/plants11101319
|View full text |Cite
|
Sign up to set email alerts
|

Late Blight Resistance Conferred by Rpi-Smira2/R8 in Potato Genotypes In Vitro Depends on the Genetic Background

Abstract: Potato production worldwide is threatened by late blight, caused by the oomycete Phytophthora infestans (Mont.) de Bary. Highly resistant potato cultivars were developed in breeding programs, using resistance gene pyramiding methods. In Sárpo Mira potatoes, five resistance genes (R3a, R3b, R4, Rpi-Smira1, and Rpi-Smira2/R8) are reported, with the latter gene assumed to be the major contributor. To study the level of late blight resistance conferred by the Rpi-Smira2/R8 gene, potato genotypes with only the Rpi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Kim et al [ 74 ] demonstrated that in the genotypes MaR8 and MaR9, at least four genes of types R3a , R3b , R4 , and R8 are present, as well as seven of types R1 , Rpi-abpt1 , R3a , R3b , R4 , R8 , R9 , respectively. The Fortuna variety has two pyramided genes, namely Rpi-blb1 and Rpi-blb2 [ 170 ]. The Bzura cultivar harbours two Rpi genes: R2-like and another unknown Rpi gene [ 171 ].…”
Section: Genetic Methodologies For Breeding Resistance To P...mentioning
confidence: 99%
“…Kim et al [ 74 ] demonstrated that in the genotypes MaR8 and MaR9, at least four genes of types R3a , R3b , R4 , and R8 are present, as well as seven of types R1 , Rpi-abpt1 , R3a , R3b , R4 , R8 , R9 , respectively. The Fortuna variety has two pyramided genes, namely Rpi-blb1 and Rpi-blb2 [ 170 ]. The Bzura cultivar harbours two Rpi genes: R2-like and another unknown Rpi gene [ 171 ].…”
Section: Genetic Methodologies For Breeding Resistance To P...mentioning
confidence: 99%
“…The Sárpo Mira cultivar is one of the few potato cultivars that has been reported to retain resistance in the field for more than a decade. Its genetic origin has not been publicly disclosed, but its genome contains a set of at least five different R genes that confer qualitative and quantitative resistance to late blight [101][102][103]. It has been used in studies of late blight resistance and as a source of resistance in conventional breeding [102,104].…”
Section: Traditional Breedingmentioning
confidence: 99%
“…Its genetic origin has not been publicly disclosed, but its genome contains a set of at least five different R genes that confer qualitative and quantitative resistance to late blight [101][102][103]. It has been used in studies of late blight resistance and as a source of resistance in conventional breeding [102,104]. On average, the traditional potato breeding process takes more than ten years from the initial crossing (Figure 5) to obtaining a new cultivar, but the process can take considerably more time due to a laborious selection process, backcrossing, and the elimination of undesirable quality traits [105].…”
Section: Traditional Breedingmentioning
confidence: 99%